Motives and functions of patenting in public basic science - Neumann, Michael (Springer Gabler, 2021)
Taking German public basic research as an example, this book explores how the ongoing implementation of knowledge and technology transfer as the Third Mission of academic science creates not only new incentives for academic patenting, but also triggers new patenting motives and strategies of researchers and organizations. Analyzing these motives and strategies, the book highlights how the complex regulatory interplay of the patent system, research policy and self-governed academic communities creates a situation in which new patent functions emerge: beyond their intended function as a protection for upstream inventions, patents become a signaling device for scientists to communicate their commitment and competence in the Third Mission. As an exploratory study, this book combines qualitative empirical research with concepts and insights from multiple fields such as economics, law, political sciences and regulation. In consequence, the book addresses anyone interested in patenting incentives and motives and their impact on the functional change and regulatory effectiveness of patents in polycentric regulatory environments. About the author: With a background in institutional economics and philosophy of science, Michael Neumann joined the DFG graduate school on intellectual Property and the Public Domain and the MPI for Innovation and Competition to write this doctoral thesis. He now works as a consultant on research and innovation policy.